(untitled) (SCIENCE TIME JOURNAL, 2026)
This article explores how proverbs function as pragmatic instruments of manipulation across three linguistic and cultural traditions: Uzbek, Russian, and English. While proverbs are typically regarded as concise carriers of collective wisdom, they also operate as subtle tools of influence by encoding indirect speech acts, conversational implicature, and presupposition. Through a comparative qualitative analysis grounded in pragmatics and discourse theory, this study demonstrates that proverbs rarely serve as neutral expressions. Instead, they reinforce cultural norms, regulate social behavior, and lend impersonal authority to speaker intentions. The analysis highlights how different cultures embed indirectness and evaluative force in their proverbial traditions, shaping communication styles and power dynamics. By focusing on both linguistic form and contextual function, the study contributes to a deeper integration of pragmatics and paremiology and underscores the persuasive potential of traditional discourse.